Enhancing the clinical coverage and anticancer efficacy of immune checkpoint blockade through manipulation of the gut microbiota. (2nd January 2017) - Pitt, Jonathan M.; Vétizou, Marie; Gomperts Boneca, Ivo; Lepage, Patricia; Chamaillard, Mathias; Zitvogel, Laurence
ABSTRACT: Although anticancer therapy with immune checkpoint blockers has seen unprecedented success, it fails to control neoplasia in most patients and often causes immune-related adverse events (irAEs). Our recent research shows the immunostimulatory and antitumor effects of CTLA-4 blockade depend on distinct Bacteroides species of the gut microbiota, signifying novel approaches to improve such immunotherapies.